Changes in Hepcidin and Reticulocyte Hemoglobin Equivalent Levels in Response to Continuous Erythropoietin Receptor Activator Administration in Hemodialysis Patients: A Randomized Study. Issue 5 (24th January 2014) - Kakimoto‐Shino, Midori; Toya, Yoshiyuki; Kuji, Tadashi; Fujikawa, Tetsuya; Umemura, Satoshi
Abstract Inadequate iron availability limits the response to erythropoiesis‐stimulating agents (ESA) and hepcidin is a key regulator of iron metabolism. However, there is little information concerning time‐dependent changes in hepcidin in response to the change of accelerated iron demand due to ESA‐induced erythropoiesis. In this study, iron‐related parameters, including hepcidin levels, were explored in comparison to patients receiving continuous erythropoietin receptor activator (CERA) and epoetin beta (EPO) treatment. Ninety‐four patients were randomized to receive monthly CERA (N = 47) or EPO three times/week (N = 47). After the titration period, hemoglobin levels and iron‐related parameters were examined. Data for 71 patients were evaluated (CERA, N = 34; EPO, N = 37). Compared with EPO treatment, CERA treatment caused significant decreases within 1 week in hepcidin (−93.5 ± 46.9 vs. −1.3 ± 38.3 ng/mL, P < 0.01), reticulocyte hemoglobin equivalent (Ret‐He) (−4.03 ± 2.64 vs. −1.13 ± 1.41 pg, P < 0.01), ferritin (−58.9 ± 30.5 vs. −12.2 ± 23.8 ng/mL, P < 0.01) and transferrin saturation (−13.2 ± 9.1 vs. 1.0 ± 11.9%, P < 0.01) and significant increases within 2 weeks in the levels of hemoglobin (0.42 ± 0.38 vs. −0.02 ± 0.48 g/dL, P < 0.01). In conclusion, hepcidin, Ret‐He, ferritin and transferrin saturation levels decreased within 1 week and hemoglobin increased within 2 weeks after CERA administration. Time course of iron‐related parameters including hepcidin demonstrated accelerated iron utilization appropriately according to ESA‐induced erythropoiesis.